KNOWLEDGE, ATTITUDES AND PRACTICES OF HEPATITIS B AND C AMONG BARBERS OF URBAN AND RURAL AREAS OF RAWALPINDI AND ISLAMABAD - Shah, Hassan Bin Usman; Dar, Mohsin Khalil; Jamil, Anique Ahmad; Atif, Iffat; Ali, Raja Jazib; Sandhu, Ali Shan; Usmani, Abdul Qadir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Hepatitis B and Hepatitis C are serious global public health problems with a prevalence of 10-15% with majority of the cases seen in the developing countries including Pakistan. It is a blood borne infection transmitted by infected blood and blood products through transfusions, contaminated needles, vertical transmission, unsafe sex and reuse of razors by barbers. The literature search so far did not reveal any study comparing knowledge, attitude and practices of hepatitis B & C in barbers working in Urban and rural areas. Methods: A comparative cross sectional survey was carried out among barbers of urban and rural areas of Rawalpindi and Islamabad. A structured close ended questionnaire was filled from total of 202 barbers by non-probability convenience sampling technique. Comparative data analysis was done including variables like age, education, knowledge about hepatitis B & C, mode of transmission, role of the blades and media etc. Results: Knowledge about hepatitis B & C was good in urban areas (92%) as compared to those working in the rural areas (68%). Using new blade for every customer was seen in urban (100%) and rural (93%) area. However barbers knowledge about symptoms of the disease (urban 81% & rural 93%) and vaccination trend of Hepatitis B was low. Conclusion: This study showed a marked difference in the knowledge, attitude and practices of the barbers working in the urban and the rural areas. Main focus should be on launching Health education programs and behaviour change communication campaigns for the barbers. Strict regulatory monitoring must be done against unlicensed street barbers.